1987
DOI: 10.1002/1097-0142(19870301)59:5<972::aid-cncr2820590520>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Transitional cell tumors of the renal pelvis and ureter associated with capillarosclerosis indicating analgesic abuse

Abstract: An association between transitional cell tumors (TCT) and abuse of compound analgesics has been established during the past two decades. Recently thickening of basement membranes around subepithelial capillaries, known as capillarosclerosis, has been reported as a change in the urinary tract pathognomonic for a long-standing abuse of compound analgesics. Therefore the authors reviewed pathologic and clinical data in 59 patients treated for TCT of the renal pelvis or ureter. Capillarosclerosis was found in nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…TCC of the upper urinary tract appears to share a similar aetiology with that of the urinary bladder. However, the aetiology is not identical, as some substances such as phenacetin [14], Chinese herbs [15] and thorium‐containing radiological contrast material [16] induce TCC more predominantly in the upper urinary tract than in the urinary bladder. In the present study we examined COX‐2 expression in human TCC of the upper urinary tract, showing for the first time that COX‐2 is frequently overexpressed in upper urinary tract TCC, associated with degree of tumour cell differentiation, indicating that COX‐2 can be a target for chemoprevention of this carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…TCC of the upper urinary tract appears to share a similar aetiology with that of the urinary bladder. However, the aetiology is not identical, as some substances such as phenacetin [14], Chinese herbs [15] and thorium‐containing radiological contrast material [16] induce TCC more predominantly in the upper urinary tract than in the urinary bladder. In the present study we examined COX‐2 expression in human TCC of the upper urinary tract, showing for the first time that COX‐2 is frequently overexpressed in upper urinary tract TCC, associated with degree of tumour cell differentiation, indicating that COX‐2 can be a target for chemoprevention of this carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Its etiology is similar to that of the urinary bladder cancer: it is frequently affected by environmental factors (chronic infection, urolithiasis, cigarette smoking, and the use of aniline stains, phenacetine, cyclophosphamide, and iphosphamide) [2,3]. More than 50% of patients with UUT-TCC are diagnosed at the T2 and advanced stages of the disease, and the 5-year survival rate of these patients varies from 30 to 60% [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…25 Some studies have reported that an increased risk of UC in patients with ESRD is associated with the usage of Chinese herbal products and analgesics, especially in the upper urinary tract. 26 A preliminary study investigating the effect of arsenic in renal parenchymal tissue of patients with UC and ESRD did not find any increase in the metal compared to patients without UC.…”
mentioning
confidence: 99%